Clinical Spectrum and Demographic Profile of Alcoholic Liver Disease Among Females Attending Tertiary Care Center in Nepal - Koirala, Dinesh; Anees, Shahbaaz; Pathak, Rahul; Kafle Bhandari, Brindeswari; Jha, Anurag; Hamal, Rabin; Gnawali, Arun; Bhusal, Mohan (Journal of Institute of Medicine Nepal, 2021)
Introduction: Alcohol is the most common abused substance in Nepal. Women tend to present with more severe liver disease with a shorter period of excessive drinking and at a lower daily alcohol intake compared to men. Methods: Adult female patients aged 16 years and above, with a diagnosis of ALD were included for a period of 1 year. Liver disease secondary to other causes were excluded. Demographic profiles, clinical features, laboratory, endoscopic findings, Child-Turcotte-Pugh (CTP), Model for End-stage Liver Disease (MELD) of the patients were recorded. Results: A total of 144 female patients with ALD were included in the study. The mean age of the patients was 48.6 years (SD=12.7). Majority of the patients were from Hilly region (n=66, 45.8%), married (n=135, 93.8%), housewife (n=83; 57.6%), Hindu by religion (n=93; 64.6%), and Tamang (n =39; 27.1%) by caste. Most common clinical features of the patients were abdominal distension (n=117; 81.2%), bilateral lower limb swelling (n=89; 61.8%), jaundice (n=54; 37.5 %) and anorexia (n=53; 36.8%). The main reason for alcohol consumption was found to be family custom in 42.3%. Esophageal varix was present in 119 (82.6%) patients. Out of 124 patients with cirrhosis, 63 (50.8%) patients were in CTP stage C and 103 (83.1%) patients had MELD score ≥ 16. Conclusion: ALD was predominantly seen among the younger female patients. The most common clinical presentations were abdominal distension, bilateral lower limb swelling, jaundice and anorexia. Among the cirrhotic patients, most of patients were in CTP class C and had MELD score ≥ 16.